Risk factors of lethal outcomes of tuberculosis in a region with low population density (Kamchatskiy kray) - A. V. Gromov; S. A. Sterlikov; Yu. V. Mikhaylova (Туберкулез и болезни лёгких)
The objective: evidence-based study of the factors inﬂuencing tuberculosis mortality in the Kamchatskiy Kray as a territory withlow population density.Subjects and Methods. A retrospective cohort study of the unfavorable course of tuberculosis in 512 patients with tuberculosis (new cases and relapses) was carried out. A univariate and multivariate analysis of risk factors for a lethal outcome of tuberculosis was performed.Results. In a univariate analysis, the incidence of death from tuberculosis among increased in older patients (p < 0.0001), among the unemployed, pensioners and disabled (p = 0.02), homeless (p = 0.01), persons who failed to undergo ﬂuorography for 2 years or more (p = 0.004), patients with a positive result of sputum smear test at registration (p = 0.003), and those suﬀering from alcoholism (p = 0.03), and decreased in patients who were actively detected (p < 0.0001 ). There was no inﬂuence on the probability of death from tuberculosis in the registration group by such parameters as new cases/relapses (p = 0.2), male/female (p = 0.09), urban/rural area of residence (p = 0.7), belonging to the indigenous population (p = 0.6), resistance to rifampicin (p = 1), cardiovascular diseases (p = 0.5), and smoking (p = 0.3). In multivariate analysis, an independent factor that reduced the risk of death was the active detection of tuberculosis patients (aOR = 0.2, p = 0.02).Conclusion. To reduce the risk of death from tuberculosis in an area with low population density (Kamchatskiy Kray), the priority should be given to improvement of active detection of tuberculosis cases; the proportion of tuberculosis patients detected during preventive screening should be used as an parameter of this improvement.